Organizational Psychology Analysis in the Context of Knowledge Management for Employee Performance Improvement - Adi Yadnya, I Dewa Gede Sayang (PT. LITERASI SAINS NUSANTARA, 2023)
Knowledge management has become a key aspect in enhancing organizational competitiveness in the current era of information and technology. Organizations that can effectively manage knowledge tend to be more innovative and adaptable to environmental changes. This research aims to make a significant contribution to the understanding of the interconnection between organizational psychology, knowledge management, and employee performance. The study employs a comprehensive examination of previously published works, utilizing qualitative analysis to achieve a thorough comprehension of the subject, spanning the timeframe from 2016 to 2023. The study's findings indicate that, in the face of the challenges posed by the globalization era and intensifying business competition, companies need to adopt a holistic approach that combines Organizational Psychology Analysis with the concept of Knowledge Management. This approach allows companies to understand and enhance employee performance by gaining in-depth insights into the psychological factors influencing individual behavior within the organization and optimizing knowledge utilization.